Oxygen Mass Transfer in Biopharmaceutical Processes: Numerical and Experimental Approaches. Issue 1 (7th December 2020) - Seidel, Stefan; Maschke, Rüdiger W.; Werner, Sören; Jossen, Valentin; Eibl, Dieter
Abstract: Oxygen supply in aerobic bioprocesses is of crucial importance. For this reason, this paper presents the oxygen demand of different cells and summarizes experimental and numerical possibilities for the determination of oxygen transfer in bioreactors. The focus lies on the volumetric oxygen mass transfer coefficient ( k L a ) calculation using computational fluid dynamics and state‐of‐the‐art models for surface‐aerated and forced‐aerated bioreactors. In addition, experimental methods for the determination of the k L a value and the gas bubble size distribution are presented. Abstract : This review provides a summary of numerical methods for the determination of oxygen transfer in surface‐aerated and forced‐aerated bioreactors as well as experimental approaches to determine the volumetric oxygen mass transfer coefficient and bubble size distribution. The focus lies on multiphase CFD and the coupling with population balance models.